The Utilization of Google Classroom on Students’ Self Regulated Learning During The Covid-19 Pandemic - Mardiati Mardiati; Lilis Saputri; Khairina Afni; Dewi Rulia Sitepu (Ridwan Institute, 2022)
This study aims to determine the effect of using google classroom on the learning independence of Mathematics Education Study Program students during the Covid-19 pandemic. This study applies a quantitative method with a descriptive approach. The research was conducted on the number of mathematics education studens as many as 124 students. The design of this research is Nonequivalent Control group design. The instrument used is a questionnaire of self regulated learning. The results of this study showed that there is an effect of using google classroom on student’ self regulated learning during the Covid-19 pandemic. Therefore, it is recommended to the teachers can provide training on the use of google classroom before learning begins.